Prinsip pembangunan mampan dalam novel ‘desir angin di pergunungan’ - Maharam Mamat (Universiti Kebangsaan Malaysia, 2009)
Sustainable development is a development that is conservatory in perspective. Sustainable development gives priority towards improving the quality of life by ensuring that developments do not exceed the carrying capacity of the natural environment while at the same time fulfills societal needs. This paper discusses how sustainable development principles are being applied in a Malay novel titled Desir Angin di Pergunungan. The author of this novel successfully ties the principles of sustainable development into his creative writing thus proves that creative writing can indeed contribute towards disseminating interdisciplinary knowledge to a larger audience